The Psychometric Properties of the Norwegian version of Beck Youth Inventories - Second Edition (BYI-II) - Kornør, Hege; Johansen, Sissel (PsykTestBarn, 2016)
Description: The Beck Youth Inventories - Second Edition (BDI-II) is a self-report questionnaire for children and adolescents aged 7-18 years intended to identify self-esteem and psychological and social problems. The American psychologists Judith Beck and John Jolly, and psychiatrist Aaron T. Beck developed both the first edition (BYI, published in 2001), and BYI-II (published in 2005). BYI-II was translated into Norwegian and published in 2012. We did not find information about the translation process. BYI-II contains 100 items; 20 for each of the five scales Self Concept, Anxiety, Depression, Anger and Disruptive Behavior. Copyright holder Pearson Assessment requires that byers of BYI-II scores should be licensed physicians or psychologists. Literature search: Our systematic literature search for psychometric studies of the Norwegian version of BYI-II resulted in 28 hits, none of which were relevant. We obtained the Norwegian BYI-II manual, which met the inclusion criteria. Moreover, we included the Danish BYI-II Manual and a Danish study, but no Swedish studies were located. Psychometrics: The Norwegian BYI-II manual contained norms based on data from 600 Norwegian children and young people by gender and three age groups (7-10, 11-14 and 15-18 years). The internal consistency (Cronbach's alpha) ranged from 0.84 to 0.92 (good to excellent). An exploratory factor analysis supported BYI-IIs five-factor structure with 38% explained variance. We found no information on test-retest reliability or criterion related validity. Conclusion: With the lack of knowledge on the BYI-II scales’ criterion related validity, it is difficult to interpret scores for clinical purposes. Great caution and clinical judgment should is therefore needed in such an interpretations. BYI-II may be useful on group and system levels as a tool to describe various aspects of mental health in children and adolescents. There is a need for further psychometric research on the Norwegian version of the BYI-II, with particular emphasis on test-retest reliability, criterion related validity and representative norms.